Anlisa Laju Abrasi Pantai Teluk Belitung Kabupaten Kepulauan Meranti Menggunakan Data Pengindraan Jauh - Fitri Landari; Sigit Sutikno; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Teluk Belitung is located in Padang island, subdistrict Merbau, Kepulauan Meranti district with area of 1348.91 km2. Teluk Belitung coast is located in Asam the Strait directly related to the Melaka Straits and the South China Sea led to the current in the Strait acids affected by wind season (Monsoon). It causes waves in the Strait of relatively large during the rainy season. Because of ocean waves directly on the coastline, Teluk Belitung coast and the surrounding Islands are a relatively easy type of peat decomposes and reduced crop coastal protection (mangroves) as a binder, causing a serious erosion problems along the coast of Teluk Belitung. That requires an analysis of the rate of coastal erosion on the Teluk Belitung which is very important in order to mitigate natural resources and maintain the viability of the local community. This study uses historical data of high-resolution aerial images based Remote Sensing technology integrated with GIS (Geographic Information System). The data used aerial photographs for 24 Year ie 1989, 1996, 1999, 2001, 2004, 2009, and the result showed that 2013. accretion occurred along the 158, 311 m or 6.60 m / year and abrasion occurred along 292.397 m or 12.80 m / year. While the extent of the accretion occurs at 84.333 ha or 3.514 ha / year and the extent of abrasion that occurs at 151.972 ha or 6.332 ha / year. Keywords: shoreline change, abrasion, accretion, remote sensing, Landsat.